"Redox lipidomics technology: Looking for a needle in a haystack". (July 2019) - Tyurina, Yulia Y.; Tyurin, Vladimir A.; Anthonymuthu, Tamil; Amoscato, Andrew A.; Sparvero, Louis J.; Nesterova, Anastasiia M.; Baynard, Matthew L.; Sun, Wanyang; He, RongRong; Khaitovich, Philipp; Vladimirov, Yuri A.; Gabrilovich, Dmitry I.; et al.
Graphical abstract: Highlights: Molecular diversity of oxygenated phospholipids is essential for their signaling role in health and disease. Selective and specific enzymatic mechanisms of phospholipid peroxidation produce low abundance, high reactivity products. Peroxidized cardiolpins are apoptotic signals. Lipoxygenase oxygenated arachidonoyl-phosphatidylethanolamines are ferroptotic signals. Acoustic presentation of LC-MS lipidomics data. Abstract: Aerobic life is based on numerous metabolic oxidation reactions as well as biosynthesis of oxygenated signaling compounds. Among the latter are the myriads of oxygenated lipids including a well-studied group of polyunsaturated fatty acids (PUFA) - octadecanoids, eicosanoids, and docosanoids. During the last two decades, remarkable progress in liquid-chromatography-mass spectrometry has led to significant progress in the characterization of oxygenated PUFA-containing phospholipids, thus designating the emergence of a new field of lipidomics, redox lipidomics. Although non-enzymatic free radical reactions of lipid peroxidation have been mostly associated with the aberrant metabolism typical of acute injury or chronic degenerative processes, newly accumulated evidence suggests that enzymatically catalyzed (phospho)lipid oxygenation reactions are essential mechanisms of many physiological pathways. In this review, we discuss a variety of contemporary protocols applicable for identification and quantitative characterization of different classes of peroxidized (phospho)lipids. We describe applications of different types of LCMS for analysis of peroxidized (phospho)lipids, particularly cardiolipins and phosphatidylethanolalmines, in two important types of programmed cell death - apoptosis and ferroptosis. We discuss the role of peroxidized phosphatidylserines in phagocytotic signaling. We exemplify the participation of peroxidized neutral lipids, particularly tri-acylglycerides, in immuno-suppressive signaling in cancer. We also consider new approaches to exploring the spatial distribution of phospholipids in the context of their oxidizability by MS imaging, including the latest achievements in high resolution imaging techniques. We present innovative approaches to the interpretation of LC–MS data, including audio-representation analysis. Overall, we emphasize the role of redox lipidomics as a communication language, unprecedented in diversity and richness, through the analysis of peroxidized (phospho)lipids.